2022
DOI: 10.3389/fpsyg.2022.833176
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Social Support, Optimism and Resilience on the Quality of Life of Cancer Patients

Abstract: IntroductionThe aim of the present study is to carry out a multidimensional analysis on the relation between satisfaction with social support received, resilience and optimism in cancer patients and their quality of life.Materials and MethodsData were gathered through questionnaires fulfilled by 142 cancer patients. Data relate to sociodemographic, health, quality of life, social support, resilience and optimism.ResultsSatisfaction with the sources and types of support, resilience and optimism relates positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 80 publications
2
35
0
Order By: Relevance
“…A strong social network was vital for patients to discuss their worries and anxieties to friends and family to relieve the burden of their diagnosis and treatment. Similar findings have been found in other cancers with a strong family support being a strong correlating factor for quality of life and a protective factors against major depressive disorders [36,37]. Additionally, it has been demonstrated that men with prostate cancer men seek support from those who have undergone similar experiences to them [38].…”
Section: Plos Onesupporting
confidence: 77%
“…A strong social network was vital for patients to discuss their worries and anxieties to friends and family to relieve the burden of their diagnosis and treatment. Similar findings have been found in other cancers with a strong family support being a strong correlating factor for quality of life and a protective factors against major depressive disorders [36,37]. Additionally, it has been demonstrated that men with prostate cancer men seek support from those who have undergone similar experiences to them [38].…”
Section: Plos Onesupporting
confidence: 77%
“…After all, such patients lack the adaptation and coping experiences, and may have more demands of social support from their family members or significant others while confronting with breast cancer. Following further literature reviews, we found that resilience and active coping style have positive effects on the self-reported quality of life in cancer patients [ 16 ], and social support and resilience are critical to HRQoL, with social support as a major mediator [ 17 , 18 ]. Regarding the comprehensive rehabilitation, it is important of higher resilience, satisfied perception of social support from family members or significant others, and positive confrontation with the adverse event to the whole recovery of physical, psychological, and social function, especially in newly diagnosed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer patients and survivors who participate in support groups report improved quality of life and less pain, which results in better compliance with medical treatment, and even extended lifespan [5,9,10]. Similarly, respondents in our study who participated in social support groups spoke highly about the bene t of these groups.…”
Section: Discussionmentioning
confidence: 63%
“…Online communities, face-to-face support groups, familial support, and informational resources are associated positively with coping among breast cancer patients [7,9]. Health outcomes in cancer patients have been found to improve with the provision of social support [5,9,10]. A recent review found that a lack of social support for breast cancer patients led to at least a 50% increase in mortality [11].…”
Section: Introductionmentioning
confidence: 99%